Shape and structure controlling of calcium oxalate crystals by a combination of additives in the process of biomineralization. Issue 20 (20th March 2018) - Liu, Nian; Xie, Hao; Ping, Hang; Wang, Lin; Liu, Zewen; Tao, Fei; Guo, Junhui; Su, Bao-Lian
Abstract : Combination of casein and small molecules regulates morphogenesis of calcium oxalate crystals. Abstract : The origin of complex hierarchical superstructures of biomaterials and their unique self-assembly mechanisms of formation are important in biological systems and have attracted considerable attention. In the present study, we investigated the morphological changes of calcium oxalate (CaO x ) crystals induced by additives including chiral aspartic acid, sodium citrate, Mg 2+, casein and combinations of these molecules. The morphology and structure of CaO x were identified with the use of various techniques. The morphogenesis of CaO x crystals were significantly affected by chiral aspartic acid, sodium citrate or Mg 2+ . However, they only formed calcium oxalate monohydrate (COM). It was observed that the chiral aspartic acid, sodium citrate and casein adhered to the surface of the crystals. The adherence of Mg 2+ to crystals was not evident. Casein significantly affected the formation of COM and calcium oxalate dihydrate (COD). The ratio of different CaO x crystal forms is associated with the casein concentration. In combination with Mg 2+ or citrate ions, casein showed improved formation of COD. The present study mimics biomineralization with a simple chemical approach and provides insight into the complicated system of CaO x biomineralization as well as facilitates the understanding of urinary stone treatment.